ChemInform Abstract: An Overview of AB2O4‐ and A2BO4‐Structured Negative Electrodes for Advanced Li‐Ion Batteries. Issue 15 (24th March 2016) - Yuvaraj, Subramanian; Selvan, Ramakrishnan Kalai; Lee, Yun Sung
Abstract: Review: 234 refs.